Pregnancy After Bariatric Surgery: Nutritional Concerns. Issue 1 (January 2019) - Snow, Denise
Abstract : Nutritional deficiencies in the post bariatric surgery pregnant woman are a complex problem. Our nutrition expert, Denise Snow, explains how knowing the potential nutritional deficiencies, the importance of monitoring, and the issues related to appropriate supplementation is essential to provide the best care for pregnant women after bariatric surgery.